Developing a robust thiadiazole derivative corrosion inhibitor for dynamic supercritical CO2 aqueous environment: Electrochemical tests and DFT calculations. (December 2022) - Li, Y.Y.; Jiang, Z.N.; Wang, X.; Zeng, X.Q.; Dong, C.F.; Liu, H.F.; Zhang, G.A.
Abstract: In this work, a novel thiadiazole derivative, 1-phenyl-3-(5-thioxo-4, 5-dihydro-1, 3, 4-thiadiazol-2-yl) thiourea (PTT) was synthesized with 5-amino-1, 3, 4-thiadiazole-2(3 H)-thione (ATT) and applied as the corrosion inhibitor for N80 carbon steel in dynamic supercritical CO2 aqueous environment. The inhibition performance and mechanism of PTT were investigated by mass loss and electrochemical measurements, surface characterization, and theoretical calculations. It is found that PTT presents the outstanding inhibitive performance with an inhibition efficiency up to 99.58%, which is significantly higher than those reported corrosion inhibitors. The density functional theory (DFT) calculations reveal that the adsorption of PTT on steel surface is implemented through the bonding of the three S atoms of (thione-thiadiazolely)thiourea fragment, as well as the benzene ring. Compared to ATT, the significant improvement in the inhibition performance of PTT is attributed to the stronger adsorption of PTT by forming more S-Fe bonds and the extra C-Fe bonds. Graphical Abstract: ga1 Highlights: A high efficiency corrosion inhibitor (PTT) was developed against the harsh dynamic supercritical CO2 aqueous environment. PTT presents the outstanding inhibitive performance with an inhibition efficiency up to 99.58%. The atomistic adsorption mechanism of PTT is in-depth revealed by DFT calculations in the aqueous environment. The robust corrosion inhibition of PTT is implemented by its strong adsorption through bonding of S atoms and benzene ring.